2009
DOI: 10.1016/j.mrgentox.2009.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Mustard gas exposure and carcinogenesis of lung

Abstract: Sulfur mustard (SM), also known as mustard gas, is an alkylating compound used as a chemical weapon in World War I and by Iraqi forces against Iranians and indigenous Iraqi Kurds during the Iran-Iraq War of the 1980s. Although SM is a proven carcinogen there are conflicting views regarding the carcinogenicity of a single exposure. The present study characterizes lung cancers formed in mustard gas victims from the Iran-Iraq War.Methods and Materials-Demographic information and tumor specimens were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Now near 8500 Iranian veterans with well-documented exposures to mustard gas are under investigation for confirming the long term carcinogenicity of this agent. 10 Lung, nasopharynx, thyroid gastrointestinal and skin cancers and also different types of leukemia are among the malignancies which were reported in these cohort but urogenital cancers was not increased in these patients. 10 Deaths from respiratory cancer occurred in 2.5% of those American veterans who exposed to sulfur mustard in World War I.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Now near 8500 Iranian veterans with well-documented exposures to mustard gas are under investigation for confirming the long term carcinogenicity of this agent. 10 Lung, nasopharynx, thyroid gastrointestinal and skin cancers and also different types of leukemia are among the malignancies which were reported in these cohort but urogenital cancers was not increased in these patients. 10 Deaths from respiratory cancer occurred in 2.5% of those American veterans who exposed to sulfur mustard in World War I.…”
Section: Discussionmentioning
confidence: 59%
“…10 Lung, nasopharynx, thyroid gastrointestinal and skin cancers and also different types of leukemia are among the malignancies which were reported in these cohort but urogenital cancers was not increased in these patients. 10 Deaths from respiratory cancer occurred in 2.5% of those American veterans who exposed to sulfur mustard in World War I. In the study of Japanese factory workers, respiratory tract tumors accounted for 58% of all reported malignant tumors (16% of all deaths).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Hosseini-khalili et al (2009) recently suggested that a single HD exposure may increase the risk of lung cancer development. Combined with many other reports mentioned in our publication (Tang & Loke, 2012), a comprehensive genomic study will certainly reveal more mutated gene and provide evidence for better understanding of the mechanism of HD-induced respiratory diseases.…”
Section: Genomic Approach and Othersmentioning
confidence: 99%